Price volatility dynamics in aquaculture fish markets. Issue 3 (3rd July 2019) - Dahl, Roy Endré; Yahya, Muhammad
Abstract: In this paper, a time-varying student- t copula is used to capture information on price volatility dependence in the short-, medium-, and long-run horizon in the US market for frozen and fresh salmon, trout, tilapia and catfish. Using monthly data from July 1992 to March 2017, the volatility dynamics for these aquaculture species are assessed. The analysis allows indicating significant differences in the volatility relationships, depending on time-frequency. While short-run volatility has limited dependency, there is significant dependency in both the medium- and long-run, indicating that market integration is stronger in the long-run. The information is particularly important to buyers and producers utilizing the futures markets, as contracts are typically traded using a set of frequencies, and may help them manage and reduce price risk.